2006
DOI: 10.1158/1078-0432.ccr-05-2425
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Docetaxel and S-1 Combination Therapy for Advanced or Recurrent Gastric Cancer

Abstract: Purpose: To evaluate the efficacy and toxicity of docetaxel in combination with a novel oral 5-fluorouracil analogue S-1for patients with advanced or recurrent gastric cancer. Experimental Design: Patients with advanced or recurrent adenocarcinoma of the stomach and up to one previous chemotherapy regimen were treated with i.v. docetaxel 40 mg/m 2 on day 1and oral S-1 80 mg/m 2 /d on days 1to 14 every 3 weeks. Results: Forty-eight patients (median age, 65 years; range, 25-75 years) received a total of 272 trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
134
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(140 citation statements)
references
References 30 publications
5
134
1
Order By: Relevance
“…These have explored docetaxel dosing intervals ranging from every week to every 4 weeks with relative dose intensities from 10 to 20 mg m À2 per week. However, because final reports of these studies are not yet available, the feasibility and efficacy of these alternative regimens remains unknown (Yoshida et al, 2004;Kim et al, 2006;Park et al, 2006;Rino et al, 2006;Satoh et al, 2006;Takahashi et al, 2006). In the phase II part of this study, we demonstrated that for patients with advanced GC, this regimen conferred an ORR of 46% and an estimated median survival of 14 months, with acceptable toxicity.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…These have explored docetaxel dosing intervals ranging from every week to every 4 weeks with relative dose intensities from 10 to 20 mg m À2 per week. However, because final reports of these studies are not yet available, the feasibility and efficacy of these alternative regimens remains unknown (Yoshida et al, 2004;Kim et al, 2006;Park et al, 2006;Rino et al, 2006;Satoh et al, 2006;Takahashi et al, 2006). In the phase II part of this study, we demonstrated that for patients with advanced GC, this regimen conferred an ORR of 46% and an estimated median survival of 14 months, with acceptable toxicity.…”
Section: Discussionmentioning
confidence: 64%
“…For example, the respective mean AUC and C max of 5-FU were 522.5 ng h ml À1 and 100.3 ng ml À1 with docetaxel 40 mg m À2 and 857.2 ng h ml À1 and 155.8 ng ml À1 , with docetaxel 50 mg m À2 (Yoshida et al, 2004). Synergy of this combination has been reported in vitro, suggesting that biochemical modulation of the two drugs occurs.…”
Section: Discussionmentioning
confidence: 83%
“…For combination chemotherapy regimens, which included S-1, either a 2-week administration with a 1-week interval protocol (Hyodo et al, 2003;Yoshida et al, 2006), or 3-week administration with a 1-to 2-week interval protocol have been reported (Koizumi et al, 2003;Ajani et al, 2005b). However, a recent post-marketing surveillance of S-1 disclosed that most toxicities increased during S-1/docetaxel/CDDP in metastatic gastric cancer T Takayama et al the third week of S-1 administration, often resulting in discontinuation of treatment (Nagashima et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The reason we administered docetaxel and CDDP on day 8 and not on day 1, as in previously reported S-1/CDDP combination studies (Ajani et al, 2005b), was that when we, in the pilot study, administered both drugs on day 1, we encountered severe neutropenia on days 10 -14. We used an S-1 dosage of 40 mg m À2 twice daily in this study according to the previous studies (Koizumi et al, 2000;Yoshida et al, 2006). Although this is a phase I study recruiting only 17 patients, the RR was quite high (88%) compared with those of phase II and phase III studies previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical trials of S-1 and other chemotherapeutic agents such as cisplatin and docetaxel have been carried out in patients with gastric cancer [2,15,25]. Some promising results have been reported with a response rate of 40-70% and a median survival of 11-14 months with these combination regimens.…”
Section: Time (Weeks)mentioning
confidence: 99%